Assessing the antimicrobial activities of Ocins - Choyam, Shilja; Lokesh, Dhanashree; Kempaiah, Bettadaiah Bheemakere; Kammara, Rajagopal (Frontiers in Microbiology, 2015)
The generation of a zone of inhibition on a solid substrate indicates the bioactivity of antimicrobial peptides such as bacteriocin and enterocin. The indicator strain plays a significant role in bacteriocin assays. Other characteristics of bacteriocins, such as their dispersal ability and the different zymogram components, also affect bacteriocin assays. However, universal well diffusion assays for antimicrobials, irrespective of their ability to diffuse (bacteriocin, enterocin), do not exist. The ability of different zymography components to generate non-specific activities have rarely been explored in the literature. The purpose of the present work was to evaluate the impact of two major factors (diffusion and no diffusion) in a solid substrate bioassay, and to document the adverse effects of sodium dodecyl sulfate in zymograms used to estimate the approximate molecular weight of bacteriocins.